Healthy aging and care of the older adult with chronic disease: a qualitative needs assessment in 14 eastern and southern Caribbean islands - Nancy VanDevanter; Madeline Naegle; Nasreen Nazia; Avion Bamodu; Eileen Sullivan Marx (Pan American Health Organization, 2023)
The objectives of this qualitative needs assessment were to assess perceived needs of health and social services professionals in the Caribbean Region to enhance services supporting healthy aging and care of older adults and to assess perceived facilitators and barriers to increasing capacity to serve their aging populations. The assessment, informed by the Consolidated Framework for Implementation Science, was conducted in 14 islands in the eastern and southern Caribbean. The results demonstrated need for education of professionals and the general population about the prevention and treatment of non-communicable diseases (NCDs), assessment and services for individuals with dementia, Alzheimer's disease, depression, and harmful alcohol use, all of which pose significant challenges for older adults. Education of health and social services professionals, families, and the public on the risk factors for NCDs and common mental and physical health problems is critical. Barriers to implementation of educational programs include lack of community awareness and resources within the islands. The needs assessment findings are foundational to planning educational interventions. These will be developed by local health providers with the collaboration and support of external resources including those of the Pan American Health Organization/World Health Organization Collaborating Centre in Gerontological Nursing Education.